THE URGENCY OF ISLAMIC LAW SOURCES KNOWLEDGE MAṢĀDIR AL-AḤKĀM AL-MUKHTALAF FĪHĀ ISTIṢAB, SADD AL-DZARĪ’A, AND QAUL AL-ṢAḤABĪ - Ahmad Maulidizen (Hukum Islam, 2018)
This article is the writer’s team thinking result about the importance (urgency) of Islamic law or sharia sources Madasir al-Ahkam al-Mukhtalaf Fiha (ijtihad postulates which are disputed) which focused on Istishab, Sadd al-Dzari’a, and Qaul al-Sahabi. Nowadays, there are still many of Indonesian who are not understand well yet or even not understand at all about these Islamic law sources. This article uses data collection method by observation and library data which then analysed by using inductive, deductive, and comparative method. This article purposes to give knowledge to the readers about Istishab, Sadd al-Dzari’a, and Qaul al-Sahabi, which then can be applied in living their life as a Moslem.